Counseling on Digital Marketing in Marketing MSMEs in the Tourism Sector in the Tourism Market of the Mulawarman Museum, Kutai Kartanegara District - Khalish Arsy Al Khairy Siregar; Faldi; Rahman Anshari; Hasyrul Hamzah; Jati Pratiwi; Junianda Haris Dwiagam (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is a country rich in cultural and tourist resources, one of which is the Kutai Kartanegara Regency, one of the regencies in East Kalimantan Province. Kutai Kartanegara Regency is rich in cultural and tourist resources. During the current epidemic, the tourist industry has had a catastrophic influence on business actors in the tourism sector, particularly in Kutai Kartanegara. According to sources, the tourism sector in Kutai Kartanegara has dropped by 80% due to the COVID-19 epidemic. The ease with which information is accessible is due to recent technology improvements that bring community convenience. One of them is the role of technical advancements, such as the existence of Digital Promotion in operating a business or business for the community, which may facilitate access to information and product marketing. Digital marketing is a beneficial method for promoting a product via information technology, with social media serving as an informational forum and chance for company actors and their consumers. The Mulawarman Museum Tourism Market was chosen as a service location based on field circumstances, business players' revenue level in the calm Mulawarman Museum Tourism Market, and a decline in income. It is intended that this service activity would give marketing solutions for MSME players in the tourist industry at the Mulawarman Museum Tourism Market.